2014
DOI: 10.1016/j.jpedsurg.2013.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aurora kinase-A downregulates cell proliferation and angiogenesis in neuroblastoma

Abstract: Purpose Aurora kinase A (AURKA) overexpression is associated with poor prognosis in neuroblastoma and has been described to upregulate VEGF in gastric cancer cells. However, the exact role of AURKA in the regulation of neuroblastoma tumorigenesis remains unknown. We hypothesize that AURKA-mediated stabilization of N-Myc may affect VEGF expression and angiogenesis in neuroblastoma. Therefore, we sought to determine whether inhibition of AURKA modulates neuroblastoma angiogenesis. Methods Cell viability and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 24 publications
2
24
0
3
Order By: Relevance
“…Given this, and our data demonstrating reduced in vitro neuroblastoma cell migration with inhibition of AURKA, we next attempted to identify the effect of silencing AURKA on FAK expression. We used stably-transfected AURKA-silenced BE(2)-C cells (shAURKA) established in our laboratory (2, 6). Under normoxic (O 2 , 21%) and hypoxic (O 2 , 1.1%) conditions, silencing of AURKA resulted in decreased expression of FAK and p-FAK, as compared to the control (shCON) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given this, and our data demonstrating reduced in vitro neuroblastoma cell migration with inhibition of AURKA, we next attempted to identify the effect of silencing AURKA on FAK expression. We used stably-transfected AURKA-silenced BE(2)-C cells (shAURKA) established in our laboratory (2, 6). Under normoxic (O 2 , 21%) and hypoxic (O 2 , 1.1%) conditions, silencing of AURKA resulted in decreased expression of FAK and p-FAK, as compared to the control (shCON) (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory has shown that it is involved in the regulation of angiogenesis and tumorigenicity in neuroblastoma (6)}. The function of AURKA under hypoxic conditions in neuroblastoma has not been extensively studied but others have demonstrated that the transcriptional regulation of AURKA is increased by both hypoxia and HIF-1α (7).…”
mentioning
confidence: 99%
“…Hypoxia stimulates Aurora activity and consequently increases the malignant potential of hepatoma cells [35]. In addition, Aurora A inhibition has been observed to decrease the VEGF transcription and secretion in neuroblastoma cells and inhibit the HUVECs tubule formation [36]. So there might be a feedback loop of Aurora-VEGF-VEGFRs, we presumed that the mechanisms of Auroras and VEGFRs kinases dual inhibitors may be related with cutting off this feedback loop.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos mostram que a superexpressão de AURKA leva a má formação dos microtubulos, resultando em células aneuploides. Essa característica é muito encontrada em células tumorais, indicando que essa quinase pode ser um bom alvo terapêutico para o tratamento de diversos tipos de canceres (Meraldi et al, 2002;Romain et al, 2014). …”
Section: Estrutura E Localização Celularunclassified
“…O ensaio de colônia é um importante ensaio para avaliação da oncogenicidade in vitro e da viabilidade celular (Romain et al, 2014;Mahmoodi e Akrami, 2016). Para avaliar se a inibição farmacológica das quinases Aurora com AI II afeta a oncogenicidade das CITs oriundas da linhagem A549 e H358, nós realizamos ensaios 4.10.…”
Section: Figura 47unclassified